Predicting the impact of dynamic global urban expansion on urban soil organic carbon - Lingxia Feng; Junjie Jiang; Junguo Hu; Taolve Chen (Scientific Reports)
Abstract Urban expansion has triggered significant changes in soil organic carbon (SOC), profoundly affecting the global carbon cycle. The accurate prediction of the global distribution of urban SOC and assessment of the impact of future urban expansion on SOC are essential for urban soil carbon management. By using data from 377 urban locations, this study estimated the global distribution of urban SOC and projected future SOC changes under two socioeconomic scenarios: SSP126 and SSP585. The results showed that compared with the urban SOC density in 2000 (64.75 Mg C ha− 1), the global urban SOC density by 2100 decreased by 1.19% and 4.72% under the SSP126 and SSP585 scenarios, respectively. However, urban SOC stocks increased by 66.13% and 178.75% by 2100 under SSP126 and SSP585, respectively, reflecting a “carbon transfer” from natural ecosystems to urban land use. This study provides critical insights into the dynamics of urban SOC and underscores the necessity to balance urban expansion with ecosystem protection to reduce carbon loss and stabilise the global carbon balance.